Buildings with suspended structures in seismic areas - T.A. Belash; P.L. Rybakov (Инженерно-строительный журнал, 2016)
Using suspended structures in construction is one of the methods to improve the earthquake buildings resistance. This subject became very popular in the 60-70s of the 20th century. However, at that time there were no available methods to provide full studies devoted to the buildings of this type. Soon, however, the opportunity appeared due to the development of computer engineering. This caused further analysis and disclosure of the full potential of suspension systems. This article discusses five different structural layouts including using suspended structures. SOFiSTiK computer system was used to calculate them. The time of oscillations was the main criterion to evaluate the schemes. It is well-known that earthquake exposure on the building decreases if the time of oscillations increases. It was found that the time of oscillations of the buildings with suspended structures is greater by several times in comparison with the buildings with traditional structural system. Taken into consideration the given fact, we can suggest that the efficiency of suspension systems in seismic conditions is provided.